Bimetallic Ag3Cu porous networks for ambient electrolysis of nitrogen to ammonia. Issue 20 (3rd May 2019) - Yu, Hongjie; Wang, Ziqiang; Yang, Dandan; Qian, Xiaoqian; Xu, You; Li, Xiaonian; Wang, Hongjing; Wang, Liang
Abstract : Bimetallic Ag3 Cu porous networks exhibit superior electrocatalytic NRR performance due to their structural advantages and bimetallic composition. Abstract : The electrochemical nitrogen reduction reaction (NRR) is considered as a facile and sustainable strategy for ammonia production. Design of high-performance electrocatalysts is the crucial issue for the NRR. Herein, we present a one-pot reduction method to directly synthesize bimetallic Ag3 Cu porous networks (Ag3 Cu BPNs). Owing to their porous networks and bimetallic composition, the Ag3 Cu BPNs exhibit outstanding NRR performance with a high NH3 yield of 24.59 μg h −1 mgcat. −1 and faradaic efficiency of 13.28% at −0.5 V vs. the reversible hydrogen electrode. This study proposes a facile and scalable route for the development of metallic porous networks with an interconnected structure and desired components for electrochemical ammonia production.